Dynamic System Simulation Design Projected Growth and Shrinkage of to Food Production in Sukabumi - Rezaghani; Baskoro, Arif Dwi; Aprido, Eka; Tosida, Eneng Tita; Subandi, Kotim; Sugara, Victor Ilyas (International Journal of Global Operations Research, 2025)
A rapid increase in population along with limited agricultural land can lead to shrinkage of paddy fields, which risks threatening food production and the sustainability of the agricultural sector in the region. This research uses a simulation modeling method with a dynamic system approach. The simulation model was designed based on data related to population growth and the decline in rice field area, as well as other factors that influence it. The dynamic system approach is often applied to analyze systems with many interdependent components. The iteration process in this system shows how changes in one element can affect other elements in the future through complex cause-and-effect relationships. Increased demand for land has contributed to the shrinkage of paddy fields, which in turn has reduced food production. In Sukabumi district, population growth increases land demand, thus accelerating the shrinkage of paddy fields and reducing food production in the region. Projections show that the population of Sukabumi District will grow by around 29% per year, reflecting the huge challenge of providing adequate services and infrastructure to the population.